An Improved Model of the Heat Pipe Based on the Network Method Applied on a Heat Pipe Cooled Reactor - Guo, Yuchuan; Su, Zilin; Li, Zeguang; Wang, Kan; Liu, Xuanyi (Frontiers in Energy Research, 2022)
As the unique piece of heat transport equipment in a heat pipe cooled reactor, an accurate simulation of the heat pipe is helpful for understanding the real behavior of the reactor core and the reactor system. Based on the network method, an improved model for the heat pipe which considers the heat conductance in the wall, the vapor flow in the vapor space, and the liquid flow in the wick is proposed. Meanwhile, the gravity term is also added to the flow equation. Compared with the experimental results of a copper-water heat pipe, the validity of this model is verified. Then, a high-temperature sodium heat pipe of 1.0 m length is selected as the study object. Based on the analysis, it can be found that the total temperature difference of the heat pipe is 31.7 K, and the temperature drop caused by the vapor flow is only 2.6 K. As for the flow pressure drop in the heat pipe, the pressure drop is mainly concentrated in the wick region, which is 8,422.47 Pa, and the pressure drop in the vapor space is only 896.68 Pa. In cases of non-uniform heating and cooling, high heat leakage, and inclined operation, results indicate that the greater the non-uniformity of heating or cooling, the greater will be the temperature drop of the heat pipe. With the increase of heat leakage, the operating temperature of the heat pipe decreases significantly, and the total temperature drop increases. The heat pipe can operate at all positive inclination angles, but when the inclination angle exceeds−30°, the heat pipe will reach the capillary limit, and it may be damaged. All of these results can provide support for the design and simulation of a heat pipe cooled reactor.